2022
DOI: 10.1021/acsami.2c04849
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Drug Release from Antibacterial Polycaprolactone/Rifampicin-Based Core–Shell Electrospun Membranes: A Proof of Concept

Abstract: The employment of coaxial fibers for guided tissue regeneration can be extremely advantageous since they allow the functionalization with bioactive compounds to be preserved and released with a long-term efficacy. Antibacterial coaxial membranes based on poly-ε-caprolactone (PCL) and rifampicin (Rif) were synthesized here, by analyzing the effects of loading the drug within the core or on the shell layer with respect to non-coaxial matrices. The membranes were, therefore, characterized for their surface proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…Tis can be done by adding drug releasing systems, for which PCL is an excellent candidate due to its high drug permeability. Tere has been promising research conducted on combining drug releasing systems with PCL using antibiotics and nitric oxide as well as other compounds [32,[48][49][50][51][52]. Te combination of drug releasing systems or nitric oxide with the NaOH surface modifcation can possibly increase the endothelization of the graft in a next step while, in addition, decreasing the bacterial infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Tis can be done by adding drug releasing systems, for which PCL is an excellent candidate due to its high drug permeability. Tere has been promising research conducted on combining drug releasing systems with PCL using antibiotics and nitric oxide as well as other compounds [32,[48][49][50][51][52]. Te combination of drug releasing systems or nitric oxide with the NaOH surface modifcation can possibly increase the endothelization of the graft in a next step while, in addition, decreasing the bacterial infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…A conventional parallel electrospinning configuration was carried out under ambient conditions. First, r-PET granules and upcycled TPEE granules were dissolved in TFA/DCM (100:0, 70:30, and 50:50) at 20 wt % or in TFA/DCM (50:50) at various polymer concentrations (10,20, and 25 wt %). Then, commercial TPEE granules were dissolved in TFA/DCM (50:50) at a 20 wt % concentration for comparison to upcycled TPEE.…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Electrospinning is a valuable technique for fabricating polymeric nano- and microfibrous structures because of their high surface-to-volume ratios. , Furthermore, the types of materials applied in electrospinning are versatile because the viscosities of polymer solutions can be systematically controlled. As a result, electrospun fibers have received tremendous attention because of their unique properties and applications in various areas, such as sensors, wearable devices, and drug delivery. The electrospinning technique has been proposed for converting recycled plastics into fibrous membranes to decrease of the amount of pollutants that end up in the environment. Electrospinning based on upcycled plastics, however, has rarely been investigated. Therefore, in this study, the electrospinning technique is chosen to upcycle r-PET films.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for these results might be that the structure and processing method of the uniaxial fiber cannot well optimize the release behavior of pheromones . Some studies have demonstrated that the utilization of coaxial electrospinning technology to fabricate drug-loaded core–shell fibers can significantly alleviate the problem of burst release. Therefore, we conceived to optimize the release curves of pheromones by preparing fibers with a core–shell structure.…”
mentioning
confidence: 99%